Character Education Development in The Education Curriculum: Challenges and Opportunities in The 21st Century - Mohammad Rudiyanto (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2024)
Character education has become an increasingly relevant and important issue in the 21st century. Social change, technology, and globalization have affected social values and fabrics, underscoring the urgency of character education to address increasingly complex challenges. This article outlines the complexity and importance of character education development in the context of current educational curricula. This article aims to analyze the role and importance of character education in facing the challenges of the 21st century. We discuss the social and technological changes affecting character education and explore the challenges and opportunities associated with integrating character education into the educational curriculum. This research uses in-depth literature review methods and analyses of the relevant scientific literature. We searched and analyzed a variety of studies related to character education, social change, technology, and globalization. Data and findings from these sources were used to support the arguments and analyses of this study. The results of this study reveal key findings that provide important insights into character education in the 21st century. First, character education plays an increasingly important role in shaping the quality of individuals in the 21st century. Character education not only improves moral values, but also shapes an individual's ability to think critically, make wise decisions, and contribute positively to an increasingly complex society. Furthermore, social, technological, and globalization changes have affected the order of individual values, posing challenges in integrating character education that reflects universal and local values. The main challenge in developing character education is to integrate the existing educational curriculum. This requires the development of new learning methods and adjustments to existing curriculum structures. In addition, the roles of teachers and educators in this process are very important, requiring adequate training and support.